2008
DOI: 10.1061/(asce)0733-9445(2008)134:7(1215)
|View full text |Cite
|
Sign up to set email alerts
|

Physical Theory Hysteretic Model for Steel Braces

Abstract: This paper presents a simple yet efficient physical theory model that can be used to simulate the inelastic cyclic axial force-axial deformation and axial force-transverse deformation relationships of steel braces. The model consists of a brace idealized as a pin ended member with a plastic hinge located at its midlength. Input parameters of the model are based only on the properties of the brace. The model combines analytical formulations based on the nonlinear behavior of the brace with some semiempirical no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…Physical-theory models (PTM) were used to simulate the braces response, using the out-of-plane imperfection Δ 0 calculated according to [24]. Recent studies [25,26] showed that this approach is the most appropriate to simulate both the buckling and the hysteretic behaviour of bracing elements.…”
Section: Numerical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical-theory models (PTM) were used to simulate the braces response, using the out-of-plane imperfection Δ 0 calculated according to [24]. Recent studies [25,26] showed that this approach is the most appropriate to simulate both the buckling and the hysteretic behaviour of bracing elements.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Indeed, the interstorey drift ratio θ is smaller than the limit θ DL = 0.5% and μ T is smaller than 1 (namely the brace in tension is in the elastic range). Regarding the brace under compression, although for DL the buckling occurs at all storeys, the analyses showed that the average brace out-of-plane displacements "w" (calculated as described in [23,24,28]) do not compromise the functionality of common cladding walls (e.g., sandwich panels connected to the primary steel members of the structure by means of secondary light weight cold formed frames, as illustrated in Fig. 21a).…”
Section: Recordsmentioning
confidence: 99%
“…A fiber-based buckling element approach was employed to model the bracing members as proposed by Uriz and Mahin [38]. Importantly, Dicleli and Calik [8] have demonstrated that the axial force-deformation response of a brace can be constructed based solely on its physical properties such as length, strength, flexural stiffness and out-of-straightness imperfection. In this regard, D´Aniello et al [7] have shown that the formulation used to define the out-of-straightness affects the estimation of drift demands in CB frames, especially at large deformation levels.…”
Section: Pr Pinching Modelmentioning
confidence: 99%
“…Likewise, the functional form proposed for CB structures (Equation 12) includes an additional linear term that considers the difference between the overall strength and the strength during pinching intervals caused by the accumulation of nonlinear deformations in the bracing members (Π p − Π s ). This difference between total and punching strengths can be estimated by means of available physically-based bracing models [8]. It should also be noted that an additional term of the form c n (lnΠ p lnΠ s ) was initially considered in Equation 12 but the resulting regression coefficients associated with it were found to be statistically insignificant in most cases and the term was therefore disregarded.…”
Section: Functional Forms Consideredmentioning
confidence: 99%
“…Algunos autores (Dicleli y Calik 2008;D'Aniello et al 2015) han intentado establecer intervalos de la magnitud de la deformación inicial i que estiman adecuadamente la capacidad de elementos sometidos en compresión, con base en correlaciones entre la capacidad teórica estimada y su comportamiento físico en pruebas experimentales. Los resultados se basan en modelos de elementos articulados en sus extremos únicamente y concluyen que la deformación inicial i afecta mayormente la demanda de distorsión y el mecanismo de colapso a estructuras con marcos con contravientos en configuración chevrón, lo que afecta a marcos con contravientos en cruz.…”
Section: Figura 8 Influencia De La Imperfección Inicial Al Centro Deunclassified